The rights discourse in the face of its challenges - Greco, Tommaso (DERECHOS Y LIBERTADES: Revista de Filosofía del Derecho y derechos humanos, 2024)
This paper includes some reflections on the challenges for rights deriving from populism, technology and geopolitics.